War on Terror: un bilancio - Beccaro, Andrea (Philosophy Kitchen - Rivista di filosofia contemporanea, 2015)
The War on Terror concept has justified several military interventions during the first fifteen years of the 21st century and consequently has led to an evolution of US strategic thinking. The aim of this paper is to outline, first, some elements of their terror strategy that inevitably influenced western military operations in the short term; secondly, to analyze geopolitical theaters of war (particularly Iraq) where theWar onTerror has developed.